The role of Character Education in building an inclusive and ethical generation - Tuhuteru, Laros; Rosalia, Olyvia; Lubis , Toib; Kalip, Kalip; Firayani, Firayani (Kamara Journal, 2025)
This study aims to analyze the effect of the implementation of Character Education and school environment support on inclusivity and ethical behavior among junior and Senior High School students in DKI Jakarta province. The research method used is quantitative with multiple linear regression approach. The sample consisted of middle and high school students who were randomly selected. The results of the validity and reliability test show that the research instrument is valid and reliable. The results of regression analysis showed that the implementation of Character Education and school environment support had a positive and significant effect on inclusiveness and ethical behavior, with character education having a stronger influence. The R2 test of 0.659 indicates that 65.9% of the variation in inclusiveness and ethical behavior can be explained by both independent variables, while the rest is influenced by other factors. In addition, the results of the F test prove that the regression model used is significant in explaining the relationship between variables. These findings underscore the importance of strong character education and a conducive school environment in shaping an inclusive and ethical generation. Therefore, educational institutions are expected to continue to strengthen character education programs and create a learning environment that supports the development of inclusivity and ethical values.